AQUATIC PHYSIOTHERAPY IN INDIVIDUALS WITH CARDIORESPIRATORY SEQUELATES AFTER COVID-19 (Fiep Bulletin - online, 2024)
Known as COVID-19, an acute respiratory infection, present in every country in the world, presents symptoms from the mildest to the most severe, even lethal. Physiotherapy is one of the most prominent professions that works on the front line against the virus in search of better rehabilitation. Aquatic physiotherapy is a therapeutic modality that uses water as the main tool and provides improvements in all systems. This research aimed to analyze the results of an aquatic rehabilitation protocol in a group of post-COVID 19 individuals in the city of Foz do Iguaçu- PR. The methodology included evaluation before and after applying the protocol, using spirometry to evaluate expiratory flow, manuvacuometry to measure respiratory strength and a six-minute walk to analyze functional respiratory capacity. In the reevaluation, it was possible to observe an improvement in the results of spirometry and manuvacuometry comparing the pre and post intervention results, as well as in oxygen saturation and in the 6-minute walk. The protocol showed beneficial results for rehabilitation, but greater depth is needed on the topic.